Precise discrimination of object position in the human pulvinar - Fischer, Jason (Wiley Subscription Services, Inc., A Wiley Company, 2007)
Very little is known about the human pulvinar; suggestions for its function include relaying input from cortical areas, allocating visual attention, supporting feature binding, and other integrative processes. The diversity of hypotheses about pulvinar function highlights our lack of understanding of its basic role. A conspicuously missing piece of information is whether the human pulvinar encodes visual information topographically. The answer to this question is crucial, as it dramatically constrains the sorts of computational and cognitive processes that the pulvinar might carry out. Here we used fMRI to test for position‐sensitive encoding in the human pulvinar. Subjects passively viewed flickering Gabor stimuli, and as the spatial separation between Gabors increased, the correlation between patterns of activity across voxels within the right pulvinar decreased significantly. The results demonstrate the existence of precise topographic coding in the human pulvinar lateralized to the right hemisphere, and provide a means of functionally localizing this topographic region. Hum Brain Mapp 2009. © 2007 Wiley‐Liss, Inc.